Subscribers' perception of quality of services provided by Ghana's National Health Insurance Scheme - what are the correlates? - Edward Nketiah-Amponsah; Robert Kaba Alhassan; Samuel Ampaw; Aaron Abuosi (BMC, 2019)
Abstract Background Ghana's National Health Insurance Scheme (NHIS) has witnessed an upsurge in enrollment since its inception in 2003, with over 40% of the Ghanaian population actively enrolled in the scheme. While the scheme strives to achieve universal health coverage, this quest is derailed by negative perceptions of the quality of services rendered to NHIS subscribers. This paper presents an analysis on perceptions of service quality provided to subscribers of Ghana's NHIS with emphasis on rural and urban scheme policy holders, using a nationally representative data. Methods The study used data from the 2014 Ghana Demographic and Health Survey. Ordered logistic regressions were estimated to identify the correlates of perceived quality of care of services rendered by the NHIS. Also, chi-square statistics were performed to test for significant differences in the proportions of subscribers in the two subsamples (rural and urban). Results Rural subscribers of the NHIS were found to identify more with better perception of quality of services provided by the NHIS than urban subscribers. Results from the chi-square statistics further indicated that rural subscribers are significantly different from urban subscribers in terms of the selected socioeconomic and demographic characteristics. In the full sample; age, out-of-pocket payment for healthcare and region of residence proved significant in explaining perceived quality of services rendered by the NHIS. Age, out-of-pocket payment for healthcare, region of residence, wealth status, and access to media were found to be significant predictors of perceived quality of services provided to both rural and urban subscribers of the NHIS. The significance of these variables varied among men and women in rural and urban areas. Conclusion Different factors affect the perception of quality of services provided to rural and urban subscribers of Ghana's NHIS. Health financing policies geared toward improving the NHIS-related services in rural and urban areas should be varied.